Pelatihan Teknik Membaca Scanning dan Skimming untuk Teknisi Pelayanan Darah - Ika Sulis Setianingsih; Natasya Devioleta (Universitas Pahlawan Tuanku Tambusai, 2022)
In carrying out their daily tasks, bloodbank technicians deal with various kinds of English texts, ranging from labels and manuals for using tools to the latest scientific journal articles related to blood service cases. As a result, training in scanning and skimming reading techniques was provided in a short webinar format, which was attended by bloodbank technicians from all over Indonesia. The event was attended by 123 blood service personnel who work in hospital bloodbanks and the Indonesian Red Cross. The activity was carried out by giving a short lecture followed by a discussion on the topic